The Influence Of Socioeconomic Background On Community Behaviour In Face Mask Waste Management During The COVID-19 Pandemic In Kudat, Malaysia - Mohammad Tahir Mapa; Norsahirah Binti Maulana; Adi Jafar; Nordin Sakke; Ramli Dollah; Amrullah Maraining (Poltekkes Kemenkes Yogyakarta, 2022)
The outbreak of COVID-19 spread at the beginning of 2019, and the spread of COVID-19 became increasingly uncontrolled in December 2019, resulting in most countries being severely affected in terms of economy or health. A face mask is an alternative in reducing the spread of disease through the air, either through nasal or oral droplets such as sneezing and coughing. However, using disposable face masks has created a new problem in waste management concerning facemask after-usage handling. Therefore, the objective of this study on community behavior in facemask waste management during the COVID-19 pandemic is to identify the influence(s) of community background(s) on the handling of facemask waste. A probability sampling method was used involving 220 respondents who were selected at random. The research method is in the form of a survey, which is then analyzed using regression analysis. The study's results found that the variables such as gender, education level, and total income affected the community's behavior in managing face mask waste. Therefore, the effectiveness of implementing guidelines and policies should be more thorough so that issues related to the disposal of face mask waste can be reduced.